An injectable, expandable polyacrylamide cryogel decreases blood loss and improves survival in a porcine model of junctional hemorrhage - Al-Murtadha Al-Gahmi; Syed Muntazir Andrabi; S. M. Shatil Shahriar; Carlos P. Jara; Jingwei Xie; Mark A. Carlson (Scientific Reports)
Abstract Uncontrolled hemorrhage, including junctional hemorrhage, is a leading cause of preventable death in military trauma. Effective therapies are urgently needed to stabilize patients and prevent further blood loss. We developed an injectable, Expandable Polyacrylamide Cryogel (EPC) that rapidly expands to tamponade bleeding. The hemostatic efficacy of EPC was compared to other hemostatic products in a porcine junctional hemorrhage model. Splenectomized domestic swine (~ 40 kg; N = 37) were randomized to no treatment (N = 8), EPC (N = 7), EPC + thrombin (N = 6), XStat (N = 7), and Combat Gauze (CG, N = 9). They underwent transection of the right femoral artery/vein, followed by 30 s of free bleed, 3 min of manual compression, and observation for up to 3 h. EPC application achieved hemostasis and 100% survival for both formulations, compared to XStat (85%), CG (67%), and no treatment (37%) (p 0.0228, Fisher exact). Mean total blood loss was lowest in EPC groups (~ 590 mL) versus no treatment (1,683 ± 570 mL), XStat (784 ± 407 mL), and CG (1,181 ± 721 mL; p < 0.001 ANOVA). All other endpoints tended to favor the EPC formulations. EPC application for junctional-type injury produced wound tamponade with better survival, reduced blood loss, and better hemodynamic and laboratory parameters compared to no treatment, with trending improvements over XStat and CG.